On the origin and foundation of the concept "The Person” metaphysical realism on interpersonal recognition - Nusser, Karl-Heinz (2008)
Fil: Nusser, Karl-Heinz. Pontificia Universidad Católica Argentina. Facultad de Filosofía y Letras. Departamento de Filosofía; Argentina